Cost-effectiveness of a video game versus live simulation for disaster training. (4th October 2019) - Whitfill, Travis; Auerbach, Marc; Diaz, Maria Carmen G; Walsh, Barbara; Scherzer, Daniel J; Gross, Isabel T; Cicero, Mark X
Abstract : Introduction: Disaster triage training for emergency medical service (EMS) providers is unstandardised. We hypothesised that disaster triage training with the paediatric disaster triage (PDT) video game '60 s to Survival' would be a cost-effective alternative to live simulation-based PDT training. Methods: We synthesised data for a cost-effectiveness analysis from two previous studies. The video game data were from the intervention arm of a randomised controlled trial that compared triage accuracy in a live simulation scenario of exposed vs unexposed groups to the video game. The live simulation and feedback data were from a prospective cohort study evaluating live simulation and feedback for improving disaster triage skills. Postintervention scores of triage accuracy were measured for participants via live simulations and compared between both groups. Cost-effectiveness between the live simulation and video game groups was assessed using (1) A net benefit regression model at various willingness-to-pay (WTP) values. (2) A cost-effectiveness acceptability curve (CEAC). Results: The total cost for the live simulation and feedback training programme was $81 313.50 and the cost for the video game was $67 822. Incremental net benefit values at various WTP values revealed positive incremental net benefit values, indicating that the video game is more cost-effective compared with live simulation and feedback. Moreover, the CEAC revealed a high probability (>0.6) at various WTP values that the video game is more cost-effective. Conclusions: A video game-based simulation disaster triage training programme was more cost-effective than a live simulation and feedback-based programme. Video game-based training could be a simple, scalable and sustainable solution to training EMS providers.